Penerapan Teori Donald S. Whitney Dalam Pembinaan Spritualitas Remaja Kristen di PPA GBT Kristus Ajaib Tulungagung - Gabriel Dhandi; Sutrisno Sutrisno; Yusak Tanasyah (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
Based on the results of a survey which shows that Christian youths view church and spiritual activities as no longer attractive, such as prayer, worship, quiet time, reading the Bible and other spiritual activities. This causes Christian youth to experience an identity crisis, moral degradation and is easily influenced by today's juvenile delinquency. Even though they are important assets for the church, nation and state. This also happens to Christian youth at PPA GBT Kristus Ajaib Tulungagung and the reason is because they do not have a good spiritual life and even underestimate their spiritual development. This study used a qualitative field method with an observation and direct observation approach. So that the results of direct observation and observation can describe about attainment an overview of the research objectives, namely to provide a series and presentation of authentic data on the implementation of the application of Christian youth spirituality development at PPA GBT Kristus Ajaib Tulungagung using Donald S. Whitney's theory of Spirituality Development.